Penyelesaian Sengketa Merek (Studi Kasus Pepsodent Strong vs Formula Strong) - Haura Jauza Hafizah; Rani Apriani (Wajah Hukum, 2022)
A brand is the essence of an item or service that refers to the quality and value of its owner. Famous brands are popular and familiar brands and have a high reputation. The abuse of their genuine brand is the product of those who want to seek profits that would harm their true owners. The study will examine the process of settling their disputes and the judge's ruling in the issue of pepsodent strong v formula strong. The study uses normative jurisdictional methods based on laws in Indonesia that apply to the primary law code, legislation no. 20 in 2016 on brands and geographical indications and secondary legal materials: journal, article, paper associated with brand. The results of the research on brand dispute resolution in Indonesia there are two ways, namely litigation by commercial courts and non-litigation through alternative dispute resolution or arbitration. The settlement used in the case of Hardwood Private Limited and PT Unilever tbk. carried out by Litigation in the Commercial Court at the Central Jakarta Court.